If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 = 21 + -3(x + 3) Reorder the terms: 45 = 21 + -3(3 + x) 45 = 21 + (3 * -3 + x * -3) 45 = 21 + (-9 + -3x) Combine like terms: 21 + -9 = 12 45 = 12 + -3x Solving 45 = 12 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 45 + 3x = 12 + -3x + 3x Combine like terms: -3x + 3x = 0 45 + 3x = 12 + 0 45 + 3x = 12 Add '-45' to each side of the equation. 45 + -45 + 3x = 12 + -45 Combine like terms: 45 + -45 = 0 0 + 3x = 12 + -45 3x = 12 + -45 Combine like terms: 12 + -45 = -33 3x = -33 Divide each side by '3'. x = -11 Simplifying x = -11
| 10(v+4)-2v=(4v+1)-3 | | 2x^2-x+15=0 | | 7x+5-6x=-19 | | (-2/7x)+6+(1/7x)=18 | | 9-(3x-4)=(2x+5)+(x-7) | | -4(6x+2)=21+5x | | 3z+1=7z-3 | | D/6=-8 | | x/2+2/3=63 | | Z-9=-5 | | 5(u+3)-5=-50 | | 3/8+5/16x=5/8 | | -58-5(7y+9)=-278 | | 7b-2-12b= | | 7x-(x-5)= | | 6(3n-8)-5(2n+7)= | | 3r+12/6=4r-4/4 | | X^2-5x=9-3x^2 | | 8x+12-5x-9= | | 8x+2=8(x+4) | | 5/2x=15/12 | | 3x+11-6x=15-14x+11x-4 | | 3(2x+1)-5=6x-2 | | 0.06(y-9)+0.04y=0.08y-0.01(60) | | 1/3+10u=y/v | | 6=-2910n+7 | | 8-(3+7)=23 | | 0.4x+56000(0.2+x)=1400 | | B=xm+m | | 2y^3+2+6y^2+6y= | | 4(3+5x)=47 | | 5p-13=8p+4 |